Socioeconomic Impact of Irritable Bowel Syndrome in Canada - Michel Boivin (Canadian Journal of Gastroenterology)
Irritable bowel syndrome (IBS) is the most common functional gastroenterological disorder reported to physicians. In Canada, its prevalence is about 6%. In the United States and the United Kingdom, the prevalence is estimated to be closer to 15%. Patients with IBS tend to make extensive use of health care services, even though a high percentage of them do not seek medical advice. The costs of IBS are a large expenditure of scarce resources. These costs can be divided into several categories: direct, indirect and intangible costs. The direct costs, associated with the diagnosis and treatment, are largely sustained by the health care system. The indirect costs are related to the production losses due to morbidity, and intangible costs are associated with the pain, suffering and alteration in the patient’s quality of life. The condition is a diagnosis of exclusion, and treatment, although beneficial, is rarely curative. The general treatment approach stresses the importance of a good physician-patient relationship. Exploring the nature of the expenses associated with IBS and understanding how treatment options may affect these costs are essential to reducing its financial burden.